Design Of Automatic Sliding Doors On Lab Net Centric Computing Assisted With Arduino Mega Using Radio Frequency Identification (RFID) Based On Local Area Network (LAN): Design Of Automatic Sliding Doors On Lab Net Centric Computing Assisted With Arduino Mega Using Radio Frequency Identification (RFID) Based On Local Area Network (LAN) - Enomi Muhamad Giri Salako; Ritzkal Ritzkal; Yuggo Afrianto (Jurnal Mantik, 2020)
The sliding door is currently still using the manual method by pushing it from the side by the arm so that many students pass into the Lab without knowing who accessed the door. For information on the use of the Lab room is very important. This study wants to provide a solution to these problems with a manual sliding door. The method in this study includes the analysis stage, the design stage, the implementation or implementation stage and the last one is the testing phase, the automatic sliding door in this study begins by detecting the card using RFID, when a card that already has access is detected, Arduino will command the servo motor to move the sliding door automatically and the LCD will show that it has simultaneous access with the green LED will light up. After the data from the RFID is read, Arduino will forward it to the web server via an Ethernet shield that has been connected using an RJ-45 cable then the server will forward it again to the database and then the database will be displayed on a website with a local area network network.